Studying the differential efficacy of postsymptom antitoxin treatment in type A versus type B botulism using a rabbit spirometry model - Amram Torgeman; Arieh Schwartz; Eran Diamant; Tzadok Baruchi; Eyal Dor; Alon Ben David; Avi Pass; Ada Barnea; Arnon Tal; Amir Rosner; Osnat Rosen; Ran Zichel (Disease Models & Mechanisms, 2018)
Botulinum neurotoxin (BoNT) serotypes A, B and E are responsible for most cases of human botulism. The only approved therapy for botulism is antitoxin treatment administered to patients after symptom onset. However, a recent meta-analysis of antitoxin efficacy in human botulism cases over the past century concluded that a statistically significant reduction in mortality is associated with the use of type E and type A antitoxin, but not with type B antitoxin. Animal models could be highly valuable in studying postsymptom antitoxin efficacy (PSAE). However, the few attempts to evaluate PSAE in animals relied on subjective observations and showed ∼50% protection. Recently, we developed a novel spirometry model for the quantitative evaluation of PSAE in rabbits and used it to demonstrate full protection against BoNT/E. In the current study, a comparative evaluation of PSAE in botulism types A and B was conducted using this quantitative respiratory model. A lethal dose of each toxin induced a comparable course of disease both in terms of time to symptoms (TTS, 41.9±1.3 and 40.6±1.1 h, respectively) and of time to death (TTD, 71.3±3.1 and 66.3±1.7 h, respectively). However, in accordance with the differential serotypic PSAE observed in humans, postsymptom antitoxin treatment was fully effective only in BoNT/A-intoxicated rabbits. This serotypic divergence was reflected by a positive and statistically significant correlation between TTS and TTD in BoNT/A-intoxicated rabbits (r=0.91, P=0.0006), but not in those intoxicated with BoNT/B (r=0.06, P=0.88). The rabbit spirometry system might be useful in the evaluation toolkit of botulism therapeutics, including those under development and intended to act when antitoxin is no longer effective.